Integration of comprehensive data and biotechnological tools for industrial applications of Kluyveromyces marxianus - Mochamad Nurcholis (2020)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. Among the so-called non-conventional yeasts, Kluyveromyces marxianus has extremely potent traits that are suitable for industrial applications. Indeed, it has been used for the production of various enzymes, chemicals, and macromolecules in addition to utilization of cell biomass as nutritional materials, feed and probiotics. The yeast is expected to be an efficient ethanol producer with advantages over Saccharomyces cerevisiae in terms of high growth rate, thermotolerance and a wide sugar assimilation spectrum. Results of comprehensive analyses of its genome and transcriptome may accelerate studies for applications of the yeast and may further increase its potential by combination with recent biotechnological tools including the CRISPR/Cas9 system. We thus review published studies by merging with information obtained from comprehensive data including genomic and transcriptomic data, which would be useful for future applications of K. marxianus.